Girdin Knockdown Increases Gemcitabine Chemosensitivity to Pancreatic Cancer by Modulating Autophagy - Wang, Sheng; Feng, Wei; Wang, Wulin; Ye, Xiaoman; Chen, Hao; Yu, Chunzhao (Frontiers in Oncology, 2021)
Chemotherapy is crucial for the treatment of pancreatic cancer (PC). Gemcitabine (GEM) as the first-line chemotherapy drug has a high resistance rate. Increasing the sensitivity of gemcitabine is currently the objectives and challenges of this study. Our previous study showed Girdin was closely related to the progression and prognosis of PC, indicating that Girdin may be associated with chemosensitivity. In the current study, we use recombinant adenovirus to specifically knockdown Girdin in PC cell lines to determine the effect of Girdin in the process of gemcitabine chemosensitivity. Autophagy is one of the pathways affecting the gemcitabine chemosensitivity in PC. Further research validated that Girdin may activate autophagy by interacting with autophagy protein p62/SQSTM1, which could enhance chemotherapy resistance to gemcitabine in PC. Down-regulation of Girdin may therefore increase gemcitabine chemosensitivity in PC. Our results reveal that Girdin acted as a negative regulator of gemcitabine chemosensitivity in PC. Increased autophagy activity caused by abnormally high Girdin expression may be one of the main factors for the reduction in chemosensitivity, which may provide new perspectives on understanding chemosensitization in PC.